Autopsy Diagnosis of Vaso-occlusive Crisis in Sickle cell Disease: A case Series Study from Northern Odisha - Das , U; Sahu, P; Bal, AK; Pati , S (Journal of Indian Academy of Forensic Medicine, 2024)
Sickle cell anemia is a qualitative genetic defect leading to abnormal HbS formation. During certain stressful conditions like infections, severe physical exertion, pregnancy, dehydration etc. complications may arise especially in subclinical sickle cell trait/ disease cases. Among all Sickle cell crises which include vaso-occlusive crisis, aplastic crisis, hemolytic crisis and sequestration crisis, vaso-occlusive crisis is the most commmon. Though many case reports were published on vaso-occlusive crisis in SCD, rarely we get series of cases. Here we present four cases of sickle cell crisis diagnosed during routine autopsy procedure. All the cases lost their life due to vaso-occlusive crisis involving different organs. First case was a sudden death of a pregnant lady presenting with respiratory infection and renal failure. During autopsy, all the organs were congested. Spleen was fibrotic and atrophied. Microscopic examination revealed sickled red cells with classical Gamna-Gandy body with thick fibrous bands. An HPLC report was of sickle cell disease (SCD). Case 2 was a 26 year female died suddenly in her post-partum period with features of cardiomyopathy. Spleen had Gamna-Gandy bodies. The coagulation factors and liver enzymes were deranged. HPLC study showed HbS & HbA2 only. Third case was an elderly male, a known case of sickle cell trait presented to emergency with left side hemiplegia. During the hospital stay of 7 days, he developed generalized anasarca and died because of multiorgan failure. Microsections from all viscera demonstrated sickled RBCs. Last case was a 26 year young lady who had sudden collapse while working in rice field. Histopathology examination of heart demonstrated features of acute myocardial infarction because of sickle cell crisis. HPLC confirmed the case as SCD. Sickle cell disease has complications involving many organs. Vaso-occlusion can lead to ischemic crisis of heart, brain, lungs, kidney & liver causing acute myocardial infarction, CVA, ARDS, renal failure and many more. Clinicians must have eyesight of these complications in an undiagnosed hemoglobinopathy case. Initiation of prompt treatment may reduce mortality & morbidity.